The psychological and social impact of camp for children with chronic illnesses: a systematic review update. Issue 5 (25th October 2013) - Moola, F. J.; Faulkner, G. E. J.; White, L.; Kirsh, J. A.
Abstract Advances in medicine have reduced mortality among children with complex medical conditions, resulting in a growing number of young patients living with chronic illnesses. Despite an improved prognosis, these children experience significant psychosocial morbidity, such as depression and anxiety. Therapeutic summer recreation camps have been proposed as an intervention to enhance quality of life among these children. The purpose of this systematic review was to assess the psychosocial impact of camp for children with chronic illnesses. A systematic review of central databases was undertaken using key words, and a rating tool – the Effective Public Health Practice Project (EPHPP) Quality Assessment Tool for Quantitative Studies – was employed to rate methodological quality. 21 studies were included in this systematic review. Although overall methodological quality was weak, camp participation appeared to offer short‐term psychosocial benefits on some parameters in children with a variety of chronic illnesses. There was some consistency in improved social outcomes, such as social interaction and acceptance. Based on the available evidence, it is premature to make robust claims regarding the psychosocial impact of camp as a therapeutic intervention. Theoretically informed camp programs, long‐term follow‐up, and incorporating camp‐based messaging into routine hospital care, may enhance the utility of camp as a potential psychosocial intervention in paediatrics.